LITERASI KEUANGAN PADA PASAR MODAL SYARIAH DI ORGANISASI MUHAMMADIYAH - Fajar Mujaddid; Lisma Wati (Universitas Muhammadiyah Prof Dr Hamka, 2020)
Financial literacy is a person's understanding of good and correct allocation and finance. Financial literacy is a process to improve one's knowledge, knowledge, and skills in managing and using finances in a good and right way. This study discusses finance on the Islamic capital market in the Muhammadiyah organization. By requesting a questionnaire to 70 respondents obtained the results of the literacy of Muhammadiyah residents on Islamic capital market products an average of 75% can be categorized as moderate, this value according to the range of 60% <80%. Keywords: Literacy, Capital Market, Muhammadiyah